Framing Hadis Larangan Menggambar Makhluk Hidup: Analisis Komparatif Media Muslim.or.id dan SuaraMuhammadiyah.id - Syarif, Aghis Ramadhan (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2022)
The digital era has intensified differences in understanding hadiths, especially through online Islamic media which serve as arenas for articulating religious discourse. This study explores how media framing mechanisms contribute to the accentuation of divergent interpretations, focusing on the hadith prohibiting the depiction of living beings (Ṣaḥīḥ al-Bukhārī No. 5495). Two Islamic media platforms—Muslim.or.id and SuaraMuhammadiyah.id—are examined to reveal contrasting approaches to this hadith. While Muslim.or.id frames the hadith as a strict prohibition aligned with Salafi textualism, SuaraMuhammadiyah.id presents a more contextual and interpretative stance reflective of Muhammadiyah's rationalist tradition. This research addresses three core questions: (1) How do these media platforms frame the understanding of the hadith? (2) What are the comparative framing strategies employed by each? (3) How do these differences relate to their respective ideological and institutional identities? William A. Gamson’s framing theory—specifically the concept of media packages encompassing central ideas, reasoning devices, and framing devices—this study utilizes qualitative content analysis of two key articles. It finds that media framing is not a neutral act of dissemination but a deliberate ideological representation aiming to influence perceptions and religious authority in a fragmented digital landscape. The framing of hadiths in these media not only reflects theological preferences but also serves as a strategic tool in discursive power struggles within contemporary Islam. Ultimately, this research underscores the need to view digital religious narratives as part of broader ideological formations, mediated and amplified by the dynamics of new media.